Untouchable freedom a social history of a dalit community - Prasad, Vijay (New Delhi Oxford University Prees, 2000)
Untouchable freedom traces the history of Dalit Workers-the Balmikis from the 1890s to the present. It offers a view of the work process that entraps these Dalits in to the Sanitation industry although most worked as agriculture labour prior to the twenti
Keywords: Untouchables-India; Social history; Sociology; Social conflict